Stakeholders' perceptions, reforms and consequences : report on the First National Forum of SAPRI, Bangladesh - Bhattacharya, Debapriya; Titumir, Rashed A. M. (Shraban Prokashoni, 2001)
Contributed articles presented at the Forum with reference to balance of payments status of Bangladesh.